Impactos causados por vibrações mecânicas em chapas de alumínio no processo de laminação a frio - Silva, Alyson Crystian Lopes da [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This paper purpose is to analyze one of the main problems faced by cold rolling industry of the current time, the mechanical vibration. Factors such as strips with high velocity in order to increase the productivity and thickness becoming thinner and thinner cause the vibrations to be present at all times during rolling. These market requirements also drive the industry for technology development and thus bring the challenges that the operation of a new modern equipment and more powerful. The initial purpose is to analyze the forces that cause vibration in a rolling mill type four high with two stands, where is desirable to identify the origins of these vibrational forces to make possible dismiss them or at least control its intensity, in order to prevent damage in the rolling mill and ensure product quality to the customer. For it, will be used instruments to record and store the vibrations that occur during the lamination process. With this data will be able to analyze the characteristics of the vibrations and act at your elimination. At the end of the work is expected to demonstrate how important the critical view of the engineer in the analysis of graphics combined with the calculations of the natural vibration frequency and engagement of key parts of the laminator. With these two tools at hand, will be possible to increase the productivity of the rolling mill and act preventively in maintenance, thereby reducing your downtime and increasing its performance and efficiency

Neste trabalho aborda-se uma análise sobre um dos principais problemas enfrentados pela indústria de laminação a frio da atualidade, as vibrações mecânicas. Fatores tais como alta produtividade e tiras com espessura cada vez mais finas fazem com que as vibrações estejam presente a todo momento durante a laminação. Essas exigências do mercado também impulsionam a indústria para o desenvolvimento tecnológico e com isso trazem os desafios da operação de um novo equipamento moderno e mais potente. Tem-se como objetivo analisar as forças que causam vibrações em um laminador tipo quádruo de duas cadeiras, onde se deseja identificar as origens dessas forças vibracionais para que se possa anulá-las ou pelo menos controlar sua intensidade, para evitar que danos ocorram no laminador e garantir a qualidade do produto ao cliente. Para isto serão utilizados instrumentos capazes de registrar e armazenar as vibrações que ocorrem durante o processo de laminação. Com esses dados poder-se-á analisar as características das vibrações e atuar em sua eliminação. Ao final do trabalho espera-se demonstrar o quão importante é a visão crítica do engenheiro na análise dos gráficos aliada aos cálculos da frequência natural de vibração e de engrenamento de partes cruciais do laminador. Com essas duas ferramentas em mãos irá ser possível aumentar a produtividade do laminador e atuar de forma preventiva em manutenções no mesmo, reduzindo assim seu tempo de parada e aumentando a sua performance e eficiência
Keywords: Laminação (Metalurgia); Chapas de aluminio; Testes de vibração; Vibration tests